2018
DOI: 10.1093/ee/nvy102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Color and Contrast of Highbush Blueberries to Host-Finding Behavior by Drosophila suzukii (Diptera: Drosophilidae)

Abstract: Drosophila suzukii Matsumara (Diptera: Drosophilidae) has become a serious pest in soft-skin fruits and berries, infesting both ripe and ripening fruits. Crop damage in highbush blueberry has been particularly severe. During blueberry fruit development, fruits of various degrees of ripeness are present simultaneously. In addition, foliage color changes as the season progresses. We investigated the influence of blueberry fruit and leaf color on host-finding behavior in D. suzukii. Opposing shifts between reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Volatile organic compounds associated with ripening fruits and naturally occurring yeasts have been widely acknowledged as key factors in host-finding behaviour for Drosophila species, including D. suzukii 2022 . Visual cues are also important to host-finding behaviour 23 . To that end, monitoring traps in use for D. suzukii are red or employ a combination of black and red 2427 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile organic compounds associated with ripening fruits and naturally occurring yeasts have been widely acknowledged as key factors in host-finding behaviour for Drosophila species, including D. suzukii 2022 . Visual cues are also important to host-finding behaviour 23 . To that end, monitoring traps in use for D. suzukii are red or employ a combination of black and red 2427 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is probable that visual sensitivity ranges are similar between D. suzukii and D. melanogaster . We previously demonstrated that D. suzukii are highly attuned to changes in foliage colors and are attracted to fruit colors which color contrast against foliage colors 23 . This suggests that color contrast between foreground and background colors, as is found between fruit and foliage, may be a key factor in host-finding behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In the blueberry cloche experiment where fruits were introduced on a Petri dish and not with background plant foliage, D. suzukii successfully laid eggs. It is possible that D. suzukii locates fruit visually by colour contrast (with plant foliage) as suggested by Little et al (2018) 29 rather than colour appearance. From their experiments D. suzukii had a limited ability to comprehend red.…”
Section: Discussionmentioning
confidence: 93%
“…From their experiments D. suzukii had a limited ability to comprehend red. Female D. suzukii were attracted to purple sticky discs (5 cm) on a white background 29 . In another similar recent study red, purple, and black disks were more attractive when presented against a white background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation